FINANCIAL PERFORMANCE OF VILLAGE-OWNED ENTERPRISES (BUMDES) IN PAKATTO VILLAGE, BONTOMARANNU SUB-DISTRICT, GOWA REGENCY - Ridwan Ridwan; Fina Diana; Suhendra Suhendra; Firmansa Firmansa (Yayasan Education and Social Center, 2023)
This study aims to determine the financial performance of Village Owned Enterprises (BUMDes) in Pakatto Village, Bontomarannu District. The analytical method used is financial ratio analysis using Profitability ratios (Net Profit Margin and Return On Equity), Liquidity (Current Ratio), and solvency (Debt to Equity Ratio). The results of the calculation of the Net Profit Margin profitability ratio in 2020 are 12.38% and in 2021 it is 20.12%. Return On Equity in 2020 is 64.62% and in 2021 it is 76.99%. The liquidity ratio using the Current Ratio in 2020 is 378.42%, and in 2021 it will be 828.83%. The solvency ratio using the Debt-to-Equity Ratio in 2020 is 23.31%, and in 2021 it will be 10.91%. Based on the profitability ratio data analysis, Net Profit Margin and Return on Equity are very good because the figures have exceeded the standard. In terms of liquidity, the Current Ratio does not meet its obligations (debt) properly because it needs to comply with the established standards. Regarding solvency, the Debt-to-Equity Ratio has met the standard because the resulting figure has passed the established standard.